ANALISIS NILAI MORAL DAN SOSIAL DALAM CERPEN DILARANG BERNYANYI DI KAMAR MANDI KARYA SENO GUMIRA AJIDARMA - Harris, Muis Muhammad; Hawari, Raden Solehudi; Permana, Indra (IKIP Siliwangi, 2018)
Literature of development equivalent to the development of the times, because the literature is more elegant and easy to enter and well received by the community, there are no obstacles, but literature also has a style selingkung incriminating himself with the language, easier language, the author’s style and imagination of authors make literature has a strong competitiveness among the public as a literary connoisseur, one of the most common literature in meet is short stories or short stories, stories that only briefly but have value that can be obtained after reading such a short story “Do not sing in the bathroom” author have moral values and deep social values, related to today, and high imagination, aesthetics and innate storytelling must be appreciated and given an assessment that prioritizes a unique language with familiar figures in rural and urban communities, a very concrete literary goal is to entertain, but behind it the more important thing is to appreciate and give value to the literary works that have been read, literature has a wide range because it uses language as its medium, one of them short stories, although the story is settled in one reading but the sense that in getting readers who are still in the priority by the author.